PENGARUH FAMILY CONTROL TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN PADA SEKTOR BARANG KONSUMSI - Jip, Linawati (Business Accounting Review, 2014)
The majority of companies in Indonesia owned by the families, where the family firms have advantages and disadvantages. The study of the affect of family control still gave different result so that this study was conducted. This study aimed to examine the affect of family control on profitability and firmâs value. Profitability measured by using ROA and firmâs value by using Tobinâs Q. This study was conducted in the consumer goods sector of 2010-2012 by using several control variables which were firm size, sales growth dan leverage. The hypothesis used multiple regression. The result of this study showed that the family control and firm size had significant affect on profitability and firmâs value. Sales growth had no affect on profitability and firmâs value while leverage had significant affect on profitability but no affect on firmâs value.